Roles of mTOR in Diabetic Kidney Disease - Mako Yasuda-Yamahara; Shinji Kume; Hiroshi Maegawa (MDPI AG, 2021)
Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease and the number of patients affected is increasing worldwide. Thus, there is a need to establish a new treatment for DKD to improve the renal prognosis of diabetic patients. Recently, it has shown that intracellular metabolic abnormalities are involved in the pathogenesis of DKD. In particular, the activity of mechanistic target of rapamycin complex 1 (mTORC1), a nutrient-sensing signaling molecule, is hyperactivated in various organs of diabetic patients, which suggests the involvement of excessive mTORC1 activation in the pathogenesis of diabetes. In DKD, hyperactivated mTORC1 may be involved in the pathogenesis of podocyte damage, which causes proteinuria, and tubular cell injury that decreases renal function. Therefore, elucidating the role of mTORC1 in DKD and developing new therapeutic agents that suppress mTORC1 hyperactivity may shed new light on DKD treatments in the future.